Emulation and invention - Hindle, Brooke (New York University Press, 1981)
This is a classic text about how people in the 19th-century learned how to invent new technology -- by tinkering with the mechanical parts of other successful inventions -- gears, cams, ratchets, pistons -- to come up with new combinations that improved on the original design.